Language Education Policies and Their Influence on Multilingual Classrooms in Indonesia - Syahruni Arifuddin (Generasi Sains Indonesia, 2025)
Indonesia’s remarkable linguistic diversity presents both significant opportunities and challenges for the education system. With more than 700 local languages coexisting alongside Bahasa Indonesia and English, language education policies must simultaneously promote national cohesion, global readiness, and cultural continuity. This study examines how these policy orientations are enacted in multilingual classrooms, focusing on the mismatch between official expectations and everyday instructional realities. Using a qualitative case study approach, data were obtained through policy document analysis, classroom observations, and interviews with teachers, students, and school administrators across two provinces with different multilingual profiles. The findings reveal a persistent gap between policy ideals and practice. Although multilingualism is explicitly acknowledged in national regulations, classroom instruction remains heavily dominated by Bahasa Indonesia, English is restricted to its subject domain, and local languages are rarely utilized. Teachers often employ code-switching to facilitate comprehension, but such practices are improvised rather than pedagogically structured. Students appreciate flexible language use and value their local languages, yet view English as more beneficial for future academic and economic opportunities. These results indicate that multilingual resources are present within schools but remain underutilized. For policies to translate into meaningful multilingual education, teacher support, appropriate learning materials, and more inclusive assessment models are required to recognize and leverage students’ full linguistic repertoires.